2019
DOI: 10.1002/er.4934
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of 3‐hydroxy fatty acids and their binary mixtures as phase change energy storage materials

Abstract: In the present work, we describe the chemical synthesis of 3-HFAs as prominent derivatives of fatty acids and assess if they could be applied as phase change materials (PCM). In addition, 3-HFAs were obtained by depolymerization of a bacterial biopolymeric material, polyhydroxyalkanoate. Thermal properties of 3hydoxyoctanoic, decanoic, and dodecanoic acids are reported for the first time.These materials showed the potential to be applied as PCM in temperature range from 33°C to 66°C. In order to expand the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Moreover, achieving the indoor comfort temperature by reducing the temperature changes, thus ensuring energy savings, has been aimed with the use of PCMs in the building applications 4 . Among various PCMs, especially fatty acids are very impressive materials with their high energy storage capacities, suitable phase conversion temperatures, chemical stability, isothermal characteristic, non‐corrosion, non‐supercooling and non‐toxicity properties 5‐8 . However, there are two main challenges limiting the use of PCMs in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, achieving the indoor comfort temperature by reducing the temperature changes, thus ensuring energy savings, has been aimed with the use of PCMs in the building applications 4 . Among various PCMs, especially fatty acids are very impressive materials with their high energy storage capacities, suitable phase conversion temperatures, chemical stability, isothermal characteristic, non‐corrosion, non‐supercooling and non‐toxicity properties 5‐8 . However, there are two main challenges limiting the use of PCMs in many applications.…”
Section: Introductionmentioning
confidence: 99%
“… 10 We have recently reported that the monomers derived from PHA can be used as phase change materials (PCMs) that absorb or release a large amount of latent heat. 11 We anticipated that the combination of C 60 with the aforementioned β-keto esters could offer new fullerene derivatives with both improved solubility in common organic solvents, as well as improved electron-accepting ability. In turn, resulting unique properties could further widen the scope of application of C 60 based molecules within materials and biological science.…”
Section: Introductionmentioning
confidence: 99%
“…Organic phase change materials with low corrosion and stable performance can be divided into four categories: paraffin, polyethylene glycols, fatty acids and polyhydric alcohols . For example, paraffin has been used as the PCM to prepare the glazed window, polyethylene glycols with different molecular weight has been discussed on the phase change properties, 3‐hydroxy fatty acids could be used as phase change material . And more, among these organic PCMs, polyhydric alcohols have the advantages of high phase change latent heat, high cycle stability and less severe super‐cooling, which have been used as latent heat energy storage materials, and its lower cost is conducive to its wide industrial application .…”
Section: Introductionmentioning
confidence: 99%